The Devil in the Details: A Critique of KSR’s Unwarranted Reinterpretation of “Person Having Ordinary Skill” - Dzeguze, Andrew B. (Science and Technology Law Review, 2009)
In KSR International Co. v. Teleflex Inc., the Supreme Court took it upon itself to comment on the supposed knowledge and capacities of a “person having ordinary skill in the art” as used in 35 U.S.C. § 103. This phrase is a key component of analyzing whether patents are “obvious” and lack sufficient value to justify the award of a patent. The perspective of a “person of ordinary skill in the art” is also used in virtually every meaningful standard in the field of patent law. Despite this significance, the Court felt no need to engage in any sort of structural or statutory analysis of the phrase. Instead, the Court at several points suggested that a “person having ordinary skill in the art” would have qualities that are not apparent from the plain language of the statute – such as creativity and insight beyond their immediate field. It may be that the Court did not realize that its statements regarding “persons having ordinary skill in the art” have significant implications both for patent cases involving obviousness and several other areas of the law. Therefore, this article seeks to fill the gaps left by the Court. By way of background, there is a discussion of the origins and evolution of the United States patent system and the development of the concept of “obviousness” over time. An effort at statutory construction of these terms is then made. The meanings so derived are then compared with the Court‘s statements in KSR to determine how (or if) they are consonant with precedent. Finally, as KSR is the law of the land, several potential results of a widespread implementation of the Court‘s views are posited so that the decision‘s full impact can be appreciated.